Efficacy and safety of canagliflozin in subjects with type 2 diabetes: systematic review and meta-analysis - Yang, Xu-Ping; Lai, Dan; Zhong, Xiao-Yan; Shen, Hong-Ping; Huang, Yi-Lan (European journal of clinical pharmacology, 2014)
Purpose To assess the efficacy and safety of the novel sodium glucose co-transporter 2 (SGLT2) inhibitor—canagliflozin for type 2 diabetes (T2DM). Methods A search of Medline (1946–January 2014), Embase (1950–January 2014), and The Cochrane Library for randomized controlled trials of canagliflozin compared to placebo or active comparator in T2DM was performed. Clinical Trials website and unpublished U.S. Food and Drug Administration data were also searched. Results Ten trials including 6,701 patients were analyzed. Compared with placebo, canagliflozin produced absolute reductions in glycated hemoglobin A 1c levels when used as monotherapy (weighted mean difference (WMD) −1.08 %, 95 % confidence interval (CI) [−1.25 to −0.90], p < 0.00001) or add-on treatment (WMD −0.73 %, 95 %CI [−0.84 to −0.61], p < 0.00001). When compared with other active comparators, canagliflozin significantly reduced HbA1c by −0.21 % (WMD, 95 %CI [−0.33 to −0.08], p = 0.001). Canagliflozin led to greater body weight loss (vs. placebo, WMD −2.81 kg, 95 %CI [−3.26 to −2.37]; vs. active comparators, WMD −3.49 kg, 95 %CI [−4.86 to −2.12]). Hypoglycemia with canagliflozin was similar to placebo or sitagliptin, and was lower than glimepiride (risk ratio (RR) 0.15, 95 %CI [0.10 to 0.22]). Genital tract infections were more common with canagliflozin (vs. placebo, RR 3.76, 95 %CI [2.23 to 6.35]; vs. active comparators, RR 4.95, 95 %CI [3.25 to 7.52]). Similar incidences of urinary tract infections were noted with canagliflozin compared with control groups. Conclusion Canagliflozin led to improvements in reducing glycated hemoglobin A 1c levels and body weight with low risk of hypoglycemia in patients with T2DM. Common adverse effects including genital tract infections and osmotic diuresis-related AEs were identified and reviewed. Risks of cardiovascular events are even less certain, and more data on long-term effects are needed.